Will Culling White‐Tailed Deer Prevent Lyme Disease?. (18th December 2015) - Kugeler, K. J.; Jordan, R. A.; Schulze, T. L.; Griffith, K. S.; Mead, P. S.
Summary: White‐tailed deer play an important role in the ecology of Lyme disease. In the United States, where the incidence and geographic range of Lyme disease continue to increase, reduction of white‐tailed deer populations has been proposed as a means of preventing human illness. The effectiveness of this politically sensitive prevention method is poorly understood. We summarize and evaluate available evidence regarding the effect of deer reduction on vector tick abundance and human disease incidence. Elimination of deer from islands and other isolated settings can have a substantial impact on the reproduction of blacklegged ticks, while reduction short of complete elimination has yielded mixed results. To date, most studies have been conducted in ecologic situations that are not representative to the vast majority of areas with high human Lyme disease risk. Robust evidence linking deer control to reduced human Lyme disease risk is lacking. Currently, there is insufficient evidence to recommend deer population reduction as a Lyme disease prevention measure, except in specific ecologic circumstances.